DUPHASTON APPLICATION IN OBESE WOMEN WITH UTERINE MYOMA INFLUENCE ASSESSMENT ON LIPID METABOLISM - Guz, I.A.; Parashuk, Y.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The research was carried out to evaluate the condition of lipid metabolism in women with a fibromyoma of the uterus and obesity. The obtained data made it possible to us ”Duphaston” drug in order to normalize the genital condition of women at the preoperative period.